The Management of a Private Peruvian University at Pandemic Times: Assessment of Decisions and Implications on the Key Indicators - Nieto-Chaupis, Huber (2023)
The management of a private Peruvian university along the period 2020-2021 is presented. Special attention has been paid on the qualitative angle in the sense that were described the main actions by which have had as central point the continuity of academic activities without the breaking of communications in the form top-down between the general manager and students. Essentially all actions have targeted to keep the quality of education in all the levels. The paper presents the general methodology that has consisted in the support of university to the universe of students in order that most of them continue in their program. Therefore, the management was not only the one applied to the university apparatus itself but also in to surpass the big obstacles such as the massive desertion of students in a critic epoch where Lima city has exhibited large peaks of infections as well as fatalities at the first and the second wave of pandemic at the first semester of 2021. Noteworthy actions have been taken by the general manager to conserve the desired harmony at the university even when communications have been done through the remote mode. The conclusion from the analysis of this paper is finally given.